Advances in Eating Disorders - Aguera, Zaida; Jiménez-Murcia, Susana (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Eating disorders (ED) are a group of mental disorders characterized by an altered food intake and the presence of inappropriate behaviors and thoughts about weight and shape. All EDs lead to physical and psychosocial functioning impairments in the patients which, in turn, may contribute to the persistence of the disease. The severity of EDs has been highlighted by their chronicity, medical complications, comorbidity, and high rates of mortality. Therefore, to address this important health issue, the current Special Issue collected 21 articles (i.e., three reviews and 18 research articles) focusing on the most recent and relevant scientific findings regarding advances in ED, such as genetic and epigenetic factors, biomarkers, comorbidity, clinical phenotypes, neurocognition, treatment predictors, and treatment models and therapeutic targets. Altogether, we believe that the articles contained in this Special Issue have largely achieved the initial objective of providing increased knowledge about the pathogenesis, the risk factors, the maintenance factors, and the most appropriate treatments tools for ED.